Electrical and optical analysis of InxSy:Na thin-films with varied sodium concentration as buffer layer in Cu(In,Ga)(S,Se)2 solar cells - Schoneberg, Johannes; Richter, Michael; Ohland, Jörg; Eraerds, Patrick; Dalibor, Thomas; Parisi, Jürgen (Thin solid films, 2017)
Replacing the toxic CdS buffer material in thin-film solar cells based on Cu(In,Ga)(Se,S)2 (CIGSSe) has been a crucial issue for a long time. A promising alternative buffer material is InxSy, which stands out due to its tunable characteristics, e.g. the band gap or the electron affinity by adding third elements. The specific influence of additional elements has been subject of many publications, however, with inconsistent results e.g. concerning the nature of the band gap or the conductivity of the material. The experimental access to the optical and electrical parameters of InxSy:Na thin-films is a necessity to fully understand the formation of the hetero-junction in the solar cell. For this work, CIGSSe solar cells with a varied sodium concentration and indium to sulfur ratio in the InxSy:Na buffer layer and comparable single InxSy:Na layers on sodium-free glass substrates were investigated. The solar cells were characterized by means of current-voltage measurements (IV), whereas spectroscopic ellipsometry (SE) and conductivity measurements were performed on bare InxSy:Na layers. The IV measurements indicate a formation of a transport barrier with increasing sodium content, which is in agreement with a decrease in electron affinity reported in the literature. The SE analysis shows band gap values of Eg=2.0eV for sodium-free thin-film InxSy:Na and Eg=2.45eV for the layers with the highest investigated sodium content. The absorption coefficient shows a clear indirect nature of the band gap transition. The conductivity under illumination is in the range of σ=1·10−5 (1/Ωcm) for all sodium containing layers and shows a strong decrease in the dark. However, a decrease of indium to sulfur ratios lead to a strong increase in conductivity from 1·10−6 (1/Ωcm) to σ=1·10−2 (1/Ωcm). •InxSy:Na thin-films show an indirect band transition for all compositions.•Linear bandgap evolution for increasing sodium and decreasing indium concentration•Strong increase of the InxSy conductivity for increasing indium concentration•Low conductivity for InxSy:Na independent of the sodium concentration